A system for determining user engagement behavior with a multimedia interface in a real time environment and a method thereof. - Sheikh Said, Normahdiah (2011)
This invention is a system to determine a user engagement behavior in real time environment when the user is engaging with a multimedia interface. The system receives at least one selected score from at least one user, captures and stores the at least one received selected score, at least one facial expression of at least one user, at least one visual of the multimedia interface of the at least one user engagement and the time of at least one user engagement. The data determines the user engagement behavior and is presented using a means of presenting data.